2009
DOI: 10.1002/adfm.200900125
|View full text |Cite
|
Sign up to set email alerts
|

A New Series of Quadrupolar Type Two‐Photon Absorption Chromophores Bearing 11, 12‐Dibutoxydibenzo[a,c]‐phenazine Bridged Amines; Their Applications in Two‐Photon Fluorescence Imaging and Two‐Photon Photodynamic Therapy

Abstract: A new series of quadrupolar type two‐photon absorption (2PA) chromophores 3–9 bearing a core arylamine‐[a,c]phenazine‐arylamine motif are synthesized in high yields. Palladium‐catalyzed Stille coupling and CN coupling reactions are utilized to prepare target chromophores. Detailed characterization and systematic studies of these molecules, including absorption and fluorescence emission, are conducted. These compounds are found to exhibit very large 2PA cross section values, for example, ∼7000 GM at 800 nm for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(57 citation statements)
references
References 106 publications
1
54
0
1
Order By: Relevance
“…Propeller-shaped AIE fluorogens are non-emissive in solutions but become highly fluorescent upon aggregate formation because the restriction of the intramolecular rotations (RIR) due to the physical constraint in the aggregates opens radiative decay channel30. The AIE effect makes the fluorogens ideal candidate materials for the preparation of fluorescent nanoparticles313233. We have previously shown that AIE nanoparticles with stable fluorescent signals and good cellular retention can trace HeLa cells for ~4 generations in vitro 34.…”
mentioning
confidence: 99%
“…Propeller-shaped AIE fluorogens are non-emissive in solutions but become highly fluorescent upon aggregate formation because the restriction of the intramolecular rotations (RIR) due to the physical constraint in the aggregates opens radiative decay channel30. The AIE effect makes the fluorogens ideal candidate materials for the preparation of fluorescent nanoparticles313233. We have previously shown that AIE nanoparticles with stable fluorescent signals and good cellular retention can trace HeLa cells for ~4 generations in vitro 34.…”
mentioning
confidence: 99%
“…Indeed, the photosensitizers can absorb simultaneously two less-energetic photons, the excitation in the NIR region avoids tissue absorbing or scattering and induce a deeper light penetration in the tissue. Velusamy et al (2009) synthesized new quadrupolar chromophores for twophoton absorption (Fig. 19) with a very high two-photon absorption cross-section of 7080 GM at 800 nm in toluene and a fluorescence quantum yield of 0.25.…”
Section: Multifunctional Silica Nanoparticles For Pdt and Diagnosismentioning
confidence: 99%
“…All these nanosystems could be conjugated to a biomolecule or an antibody to target receptors over-expressed in cancer cells, which enhance the selectivity of the treatment. The very recent developments of nanosystems concern up-conversion or two-photon PDT which opens new promising ways to treat deeper tissue regions (Kim et al 2007;Velusamy et al 2009). Most of the studies with nanosystems have been carried out in vitro, but in vivo PDT is currently being investigated ).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Organicm olecules with high two-photon absorptionp roperties have attracted many scientists' attention due to their potential applicationsi nt hree-dimensional (3D) fluorescencei maging,l asing up-conversion,o ptical powerl imitation, photodynamic therapy and 3D opticald ata storage. [2][3][4][5][6][7][8][9][10][11][12][13] Benefiting from their diverse advantages including well-defined structurald iversity,f lexibility and functionality,f ast response, and variable band gap, organic p-conjugated compoundsh ave been widely explored as NLO materials to enhance TPAa bsorption cross-sections. [14][15][16][17][18][19][20][21][22] In particular, extended p-conjugated systems with the symmetrical substitution of electron-donating and electron-accepting units have been regarded as efficient TPAm olecules to exhibit larger TPAa bsorption cross-sectionsc ompared to the corresponding unsubstituted counterparts, indicating that the efficient intramolecular charge transfer (ICT), [23,24] caused by the donating and withdrawing abilities of electron donor and acceptor,p lays an important role in increasing their TPAc ross-sectionsv alues.…”
Section: Introductionmentioning
confidence: 99%